Photopharmacology of Azo-Combretastatin-A4: Utilizing Tubulin Polymerization Inhibitors and Green Chemistry as the Key Steps - Rastogi, Shiva K.; Dunnigan, Jennifer K.; Towne, Adelyne C.; Zhao, Zhenze; Du, Liqin; Brittain, William J. (Current Organic Chemistry, 2021)
Tubulin Polymerization Inhibitors (TPIs) are promising ligands utilized in chemotherapy for modern cancer treatment. However, the current TPIs exhibit many serious side effects that may pose limitations in chemotherapy. Combretastatin A-4 (CA-4) is a natural TPI that binds at the colchicine binding site located on microtubules. The only cis isomer of CA-4 is bio-active; however, due to its short half-life, it isomerizes quickly to its bio-inactive trans geometric isomer. For preventing shortcomings of CA-4, azobenzene based CA-4, called azo-CA-4 (azo-CA-4) is identified as a novel TPI. The geometric isomerization of azo- CA-4 can be controlled upon exposure to ultraviolet (UV) light to remotely control its bioactivity. Cis-azo-CA-4 is 200-500 times more active (IC50 = 0.2-10 μM) than trans-azo-CA-4 (IC50 = 50-110 μM) against various cancer cell lines. Photo-pharmacology uses light to control drug activity, introducing a unique mechanism to develop novel photo-responsive TPIs. Further, the green chemistry approach using ethanol and water as a green solvent in the synthesis of azo-CA-4 delivers advanced methodology in novel TPI development.
Keywords: solvent